Synthesis, physico-chemical characterizations and antibacterial properties of copper oxide (I) nanopowders elaborated by out-of-phase pulsed sonoelectrochemistry - Fattoum, Sirine; Chopart, Jean-Paul; Charpentier, Emilie; Mejia, Jorge; Gangloff, Sophie C.; Mancier, Valérie (Materials Chemistry and Physics, 2022)
Nanopowders of copper (I) oxide (Cu2O, cuprite) were synthesized by out-of-phase pulsed sonoelectrochemical method and characterized by several physico-chemical techniques (X-ray diffraction, transmission electronic miscroscopy, energy-dispersive x-ray spectroscopy, centrifugal liquid sedimentation, zeta potentials and specific area measurements). The same analyses were done on commercial cuprite and copper nanopowders for comparison. Once the chemical nature and morphology of the three materials have been determined, bactericidal assays were performed on methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli) in Trypto-Casein-Soy medium. The results show that sonoelectrochemical Cu2O nanopowders are good antibacterial material as compared to the two commercial nanopowders while using a synthesis method that is inexpensive and adaptable to the industrial scale.
Keywords: Bactericidal materials; Cuprite; Cuprous oxide nanoparticles; Semiconducting materials; Sonoelectrochemistry